IMPLEMENTATION OF CLINICAL SUPERVISION OF SHARING OF EXPERIENCE TECHNIQUES TO IMPROVE TEACHER COMMUNICATION SKILLS IN LEARNING OF SD NEGERI NO. 257 BANGKELANGKECAMATAN BATANG NATAL IN 2020/2021 ACADEMIC YEAR - Siti Fatimah (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This type of research is Classroom Action Research (CAR) using the implementation of clinical supervision of sharing of experience techniques in learning which aims to determine the extent to which the use of this approach can improve teacher communication skills in learning by implementing clinical supervision of sharing of experience techniques in class VI SD. State 257 Workshop, Batang Natal District. The subjects of this study were students of Class VI SD Negeri 257 Bengkel Batang Natal District with a total of 24 students, 13 of whom were female and 11 were male. Based on the results of the pre-cycle test, many students have not finished learning. Of the 21 Grade VI students of SD Negeri 257 Bengkel, Batang Natal District, only 6 students (25%) scored 70 and above (completed). While the other 18 students (75%) scored below 70 (not completed). For this reason, researchers feel the need for an effort to improve teacher communication skills in student learning in Indonesian lessons by making Learning Improvements through a study. From the research carried out, it was found that there was an increase in learning outcomes after the action was carried out. In the first cycle, the percentage of student learning completeness was 54.2% and the score of class completeness was 62.5% with the lowest score of 50 and the best score of 80. In the second cycle, the percentage of student learning mastery was 100% and the score of class completeness was 87% with a score of 87%. the lowest was 70 and the best score was 90. There was an increase in students' poetry writing skills in Indonesian language lessons from cycle I to cycle II, for the percentage of student learning mastery there was an increase of 45.8% and the score of class completeness was 24.5%. The students' Indonesian learning activity in the first cycle was 62.4%, while in the second cycle it was 74.5%. There was an increase in student activity from cycle I to cycle II by 12.1%. The average value in the first cycle is 65 and in the second cycle it is 78.3. There was an increase in the value of 13.3. Likewise, teacher activity in the first cycle was 76%, while in the second cycle it was 86%. an increase in teacher activity or performance by 10%. And in the end there is a significant effect between increasing the ability to write poetry by using the implementation of clinical supervision of sharing of experience techniques on student learning outcomes, the higher the student's activity in learning, the higher the value of learning outcomes obtained.